Degree of approximation of conjugate of a function belonging to Lip(ξ(t),p) class by matrix summability means of conjugate Fourier series - Shyam Lal; Hare Krishna Nigam (International Journal of Mathematics and Mathematical Sciences)
We determine the degree of approximation of conjugate of a function belonging to Lip(ξ(t),p) class by matrix summability means of a conjugate series of a Fourier series.